Numerical analysis of PCM integrated in solar dryers for thermal efficiency - Gur, Eda Bakir; Isik, Erdem; Ucar, Aynur (Elsevier, 2026)
Solar dryers using phase change materials buffer heat, yet the combined influence of airflow regime and PCM placement on melting remains underexplored. A controlled like-for-like study fixed geometry and PCM properties while varying placement and operating conditions. A 3D transient CFD model simulated a forced-convection dryer with RT28HC over Re = 3000-9000 and inlet temperatures Ti = 50-60 degrees C. Raising either Re or Ti shortened melt time, and three-wall coverage melted faster and more uniformly than a rear-wall-only layout. For three walls, melt time dropped from 13 h (50 degrees C, Re = 3000) to 7 h (60 degrees C, Re = 9000) (-46 %) for the rear wall it fell from 19 h to 11 h (-42 %). A 10 degrees C increase in Ti reduced overall melt time by 4 h across Re. Practically, three wall PCM with Re >= 6000 at Ti = 60 degrees C achieved reliably 7-9 h melting, enabling late afternoon heat release without auxiliary heating.
Keywords: Solar dryer; PCM; Melting; CFD; Thermal energy storage; Renewable energy